Biomechanics of the sprint start - Harland, M. J.; Steele, J. R. (Sports Medicine, 1997)
Many variables have been studied pertaining to the block sprint start. Research suggests that the adoption of a medium block spacing is preferred, with front and rear knee angles in the set position approximating 90 and 130 degrees, respectively, with the hips held moderately high. The sprinter must be capable of developing a high force rate combined with a high maximum force, especially in the horizontal direction. This ability to create high force underlies other important indicators of starting performance such as minimum block clearance time, maximum block leaving velocity and maximum block leaving acceleration. Once the sprinter has projected him/herself from the blocks at a low angle (40 to 45 degrees) relative to the ground, the following 2 post-block steps should occur with the total body centre of gravity ahead of the contacting foot at foot strike to minimise potential horizontal braking forces.